‘As with everything else the end eventually comes …’ Or, how prose might work to capture a sensation of the past - Juckes, Daniel James (Curtin University, 2018)
This thesis is a hybrid work combining a creative artefact and exegesis. It is a family memoir which addresses how a sensation of the past might be evoked, with a focus on the prose of Virginia Woolf, W.G. Sebald, and Marcel Proust. The research uses objects from the past to describe the seamlessness of memory and perception, and describes a way in which the past’s vitality might be represented on the page.